The Effectiveness of Implementing Problem-Based Learning Models in Improving Biology Literacy and Scientific Attitudes - Astuti, Tika; Jufri, A. Wahab; Kusmiyati, Kusmiyati (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2025)
Biological literacy and scientific attitudes are important aspects that need to be developed in students because they are related to the ability to understand biological concepts contextually and foster scientific thinking. This study aims to analyze the effect of the Problem-Based Learning (PBL) model on students' biological literacy and scientific attitudes. The type of research used is a quasi-experiment with a pretest-posttest control group design. The sample consisted of 58 eleventh-grade students at MAN Lombok Barat, selected using purposive sampling, with the experimental class receiving PBL instruction and the control class receiving conventional instruction. Data were collected through validated biology literacy tests and scientific attitude questionnaires. Data analysis techniques included mean value comparisons and ANCOVA tests using SPSS version 26. The results showed that the average biology literacy score in the experimental class increased from 53.8 to 72.5, while the control class increased from 53.5 to 76.6. In terms of scientific attitude, the experimental class improved from 32 to 36.9, while the control class increased from 36 to 37.2. The results of the ANCOVA test revealed a significant difference between the experimental and control classes in biological literacy, with a p-value of 0.004 (p < 0.05). Similarly, in the scientific attitude, a significant difference was observed with a p-value of 0.000 (p < 0.05). Based on these findings, it can be concluded that the application of PBL has a significant effect on improving students' scientific attitudes; however, its effect on biology literacy is less optimal than that of conventional learning. This is thought to be influenced by time constraints and other external factors that cannot be fully controlled during the research.